Sam Walton, made in America : my story - Walton, Sam, 1918-; Huey, John. (New York : Doubleday, 1992)
A biography of Samuel M. Walton, whose ingenuity and persistence contributed to his becoming one of the wealthiest men in America
Includes index.
Keywords: Walton, Sam, -- 1918-; Wal-Mart (Firm) -- History; Businesspeople -- United States -- Biography; Millionaires -- United States -- Biography; Discount houses (Retail trade) -- United States -- History